أخطاء الدارسين فى استخدام الأفعال المتعدية بحرف الجر : (KESALAHAN PESERTA DIDIK DALAM MENGGUNAKAN VERBA TRANSITIF DENGAN PREPOSISI) - Syaiful Rahmat (MAN Insan Cendekia Jambi, 2021)
The study aims to identify the student’s linguistic errors in using the transitive verbs with the letter of traction. The study was conducted at First Grade Students in the State Islamic High School of Insan Cendekia of North Tapanuli Indonesia. The method used by the researcher in this study is the descriptive and error analysis method. The researcher took 30 students as sample of study. After the study was conducted and the results has showed errors of linguistics in using synonyms as follows: 1) Ignorance of rule restriction, 2) false concepts hypothesized, 3) Mother Tongue Interference, 4) Psychological factors such as forgetfulness, haste, fatigue, anxiety, laziness, illness and others.